Epizootic Yersinia enterocolitica in captive African green monkeys (Chlorocebus aethiops sabaeus) - Balamayooran, Gayathriy; Atkins, Hannah M.; Andrews, Rachel N.; Michalson, Kristofer T.; Hutchison, A. Robert; LeGrande, Andre C.; Wilson, Quentin N.; Gee, Melaney K.; Aycock, S. Tyler; Jorgensen, Matthew J.; Young, Richard W.; Kock, Nancy D.; et al. (Frontiers in Veterinary Science, 2022)
Yersinia enterocolitica is a Gram-negative bacterium that typically results in enterocolitis in humans and poses significant worldwide risks to public health. An outbreak of yersiniosis in the Vervet Research Colony at the WFSM during the winter of 2015-2016 accounted for widespread systemic infection with high morbidity and mortality. Most of the cases had extensive necrosis with suppuration and large colonies of bacilli in the large bowel and associated lymph nodes; however, the small intestine, stomach, and other organs were also regularly affected. Positive cultures of Yersinia enterocolitica were recovered from affected tissues in 20 of the 23 cases. Carrier animals in the colony were suspected as the source of the infection because many clinically normal animals were culture-positive during and after the outbreak. In this study, we describe the gross and histology findings and immune cell profiles in different organs of affected animals. We found increased numbers of myeloid-derived phagocytes and CD11C-positive antigen-presenting cells and fewer adaptive T and B lymphocytes, suggesting an immunocompromised state in these animals. The pathogen-mediated microenvironment may have contributed to the immunosuppression and rapid spread of the infection in the vervets. Further studies in vervets could provide a better understanding of Yersinia-mediated pathogenesis and immunosuppression, which could be fundamental to understanding chronic and systemic inflammatory diseases in humans.